KARAKTERISASI DAN UJI KETAHANAN GARAM EMPEDU ISOLAT BAKTERI ASAM LAKTAT AIR RENDAMAN KACANG MERAH (Phaseolus Vulgaris) - Ina Sintia Malo, Artin; Yasinta Moi, Maria (Universitas Cokroaminoto Palopo, 2026)
Lactic Acid Bacteria (LAB) are a group of Gram-positive microorganisms that do not form spores and are non-motile. LAB includes microorganisms from a group of bacteria that play an important role in food fermentation by producing lactic acid that can inhibit the growth of pathogenic bacteria and food spoilage bacteria. The role of lactic acid bacteria as probiotics for human and animal health includes the digestive system, capable of acting as an antibiotic substitute, by maintaining microbial balance in the digestive system. Resistance to acid and bile salt is a prerequisite for a microorganism to be used as a probiotic because it indicates its ability to survive in the digestive tract. The objective of this research is to determine the characteristics of lactic acid bacteria isolates obtained from fermented red bean products and to know the resistance ability of lactic acid bacteria isolates to bile salt exposure. Isolation of Lactic Acid Bacteria was performed using the pour plate method on MRSA media. The bacteria were incubated at 37°C for 48 hours. Macroscopic observation was based on morphological characteristics consistent with lactic acid bacteria as commonly seen, which is determined by the color and shape of the colonies, while microscopic observation was focused on the shape and whether they are gram-positive or gram-negative. The results of the isolation from the red bean soaking water on MRSA media yielded one isolate that was successfully isolated from the red bean soaking water and was identified as lactic acid bacteria suspected to resemble the genus Streptococcus sp. The salt tolerance test of the lactic acid bacteria isolate KM2 from red bean soaking water showed an inability to survive in bile salt conditions. This indicates that the isolate does not have sufficient resilience to the bile-rich environment of the gastrointestinal tract.